Relationship between Google search and the Vietcombank stock - Pham, Tien Phat; Hoang, Sinh Duc; Popesko, Boris; Hussain, Sarfraz; Quddus, Abdul (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
This study aims to understand the relationship between Google search and the Vietcombank stock price movement. Our weekly data consist of Google search variables and the Vietcombank variables extracted and standardized from Vietstock and Google Trend from April 2016 to April 2021. We apply the VAR Granger and Copulas approach to analyze the link between Google search and the price of Vietcombank stock. Results show that the connection between Google searches and the price of Vietcombank stock did not persist in the long run. Moreover, the evidence supporting the Granger causality between Google searches and the Vietcombank stock price was weak. Finally, the trading name (term “Vietcombank”) was preferred by Google search users over the code “VCB,” and the trading volume and Google search simultaneously increased within the sample period.